Joint immobilization: effects on bone tissue of obese and malnourished animals. - Rissi, Renato; Lemos, George Azevedo; Pires, Ivan Luiz de Souza; Camargo, Rafael Ludemann; Palomari, Evanisi Teresa (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The immobilization induces an unbalanced bone metabolism, followed by rapid bone loss and consequent loss of the mechanical function of the bone. In general, the obesity and protein malnutrition conditions affect a large number of people worldwide, and both morbidities have specific characteristics that may cause deleterious effects on bone tissues of patients by different mechanisms. Objective: the present study aimed to verify experimentally if the joint immobilization protocol causes bone tissue atrophy in obese and undernourished animals. Method: 20 adult male mice (C57/BL6) were used, divided into four groups (N=5): Control Group (CG), Immobilized Control Group (ICG), Immobilized Obese Group (IOG) and Immobilized Malnourished Group (IMG). The histomorphometric analysis of the tibia quantified the number of osteocytes, cortical thickness and diameter of the medullary canal. Results: The study involving the tibia of the animals showed statistical differences in variables analysis. All immobilized groups showed lower amount of osteocytes in the evaluated tissue and increase in diameter of the spinal canal when compared to the CG. The cortical thickness was reduced in ICG and IMG groups when compared to the CG. Conclusion: The used joint immobilization protocol caused bone atrophy in the studied animals. The association between obesity, malnutrition and joint immobilization conditions cause increase in bone tissue atrophy.